Palgrave advances in peacebuilding critical developments and approaches (Palgrave advances, 2010)
"The quality of the peace arrived at via liberal peacebuilding approaches has been poor. The related statebuilding praxis has generally been unable to respond to its critics. What is at stake is a recognition of peacebuildings everyday political, social, economic, and cultural dynamics. This indicates the emergence of a post-liberal form of peace"--Provided by publisher.